PENINGKATAN MINAT DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN BAHASA INDONESIA DENGAN MODEL EVERYONE IS TEACHER HERE DI KELAS IV SDN 35 PAGAMBIRAN PADANG - Silvia Meirisa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The study was backed by low interest and student learning outcomes in learning Indonesian Language. This is because teachers tend to use methods of lecture and a little students less cared for. To fix the issue, researchers provide a solution using the model everyone is teachere here. This study aims to describe the increased interest and the results of learning students create questions, answer questions, and suggested in the Indonesian Language learning. This type of research this is a class action Research (PTK). The subject of this research is the grade IV. Research instrument used is the observation sheet activity observation sheet, interest in teacher learning to student interest and question form sheets, test results of the study. The results showed that the learning interest of students in making the question average percentage obtained in cycle I of 63,2% increase in cycle II becomes 78,75%, interest in learning of students in answering the question on percentage gained cycle I of 62,5% increase in cycle II became 85%, then the interest to learn the students suggested retrieved persetase on cycle I of 52,5% increase in cycle II becomes 70%. In addition, the average value of the results of the learning cycle I of 67,87 increased in cycle II becomes 86,87. The results of this research it was concluded that the interest and learning outcomes grade IV can be enhanced through the model everyone is learning the Indonesian Language teacher here.